2012
DOI: 10.4048/jbc.2012.15.2.172
|View full text |Cite
|
Sign up to set email alerts
|

The Glycolytic Phenotype is Correlated with Aggressiveness and Poor Prognosis in Invasive Ductal Carcinomas

Abstract: PurposeGlucose uptake and glycolytic metabolism are enhanced in cancer cells, and increased expression of glucose transporter 1 (GLUT1) has also been reported. The aim of this study was to investigate GLUT1 expression in human breast tissues and invasive ductal carcinomas.MethodsWe used tissue microarrays consisting of normal breast tissue, ductal hyperplasia, ductal carcinoma in situ, invasive ductal carcinoma, and lymph node metastases. We examined GLUT1 expression in the microarrays by immunohistochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
6
26
0
Order By: Relevance
“…Basu et al [7] reported that TNBCs are associated with enhanced fluorodeoxyglucose uptake after comparing fluorodeoxyglucose uptake between TNBC and ER+/PR+/HER2− breast tumors. The same findings were later reproduced by two prospective studies showing that high IHC expression of GLUT1, a glucose transporter expressed in most cell types, is significantly correlated with the TNBC phenotype [8,9,10]. …”
Section: Introductionsupporting
confidence: 61%
“…Basu et al [7] reported that TNBCs are associated with enhanced fluorodeoxyglucose uptake after comparing fluorodeoxyglucose uptake between TNBC and ER+/PR+/HER2− breast tumors. The same findings were later reproduced by two prospective studies showing that high IHC expression of GLUT1, a glucose transporter expressed in most cell types, is significantly correlated with the TNBC phenotype [8,9,10]. …”
Section: Introductionsupporting
confidence: 61%
“…There are 14 GLUT members, of which GLUT1 , the first member of the GLUT family to be identified, is the most extensively studied. GLUT1 was reported originally as a marker of infantile skin hemangioma and overexpression was reported in several types of human cancers, including RCC . Renal cell carcinomas, like many other cancers, are dependent on aerobic glycolysis for ATP production, a phenomenon known as the Warburg effect .…”
Section: Discussionmentioning
confidence: 99%
“…It is a genetically and clinically heterogeneous cancer, and the most common histologic subtype is invasive ductal carcinoma, which accounts for 70% to 80% of all breast cancer cases [ 3 ]. There have been advances in understanding carcinogenesis and breast cancer biology; however, treatment problems persist [ 4 ]. Using proven clinicopathological prognostic parameters, various proteins with essential cellular functions have been proposed as potential predictors of breast cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%